ANALYSIS OF THE INTEGRATION OF RESEARCH PROJECTS OF BIOEN ORIENTED TO SUGARCANE CHAIN - Lamarca, Daniel Sá Freire; Braga Júnior, Sérgio Silva; Magalhães, Marcelo Marques (Revista Brasileira de Engenharia de Biossistemas, 2014)
This work aims to conduct analysis of the integration of research projects BIOEN - FAPESP Program, within the online promoting Research Assistance - BIOEN Program - Regular. To conduct this article, we sought in the virtual library within the BIOEN FAPESP Program, all projects for implementation and analysis was also performed a literature search to contextualize the sugarcane industry. As a result of this analysis, realized that there was little investment in some sectors of sugarcane chain, so there is room for more research in these areas, moreover, was to highlight the fact that a balance between the number of projects on stage and in the field occur step industry.